The Impact of Interfirm Linkages on Chinese MNEs' Entry into Foreign Markets - Hang Su; Sungjin Hong (East Asian Economic Review (EAER), 2022)
This paper uses social network theory and the internationalization process model (IPM) to determine how external network linkages influence the location choices of multinational enterprise from emerging economies (EMNEs); specifically, whether past alliance experience influences location choices and its impact on the subsequent entry of MNEs from emerging economies. This paper applies survival analysis using initial and secondary investments from 2,000 Chinese A-share listed companies that entered 90 countries between 1997 and 2018 to analyze both the initial and subsequent entries of Chinese outward foreign direct investments (OFDIs) in major host countries. The findings indicate that an MNE's previous experience with a company from a particular country will increase the likelihood of an initial investment in that country. Previous alliance experience may accelerate the foreign investment process of EMNE and stimulate firms making a commitment to a position in a foreign network, regardless of cultural distance and stage of internationalization. Alliance before initial investment may increase the likelihood and speed of entering a host country as wholly owned subsidiaries and that network linkages not only significantly influence the internationalization process of small and medium-sized enterprises, as indicated by the IPM, but also that of large listed firms.
Keywords: F20; F21; F23; 330; Linkage; Strategic Alliance; Outward Foreign Direct Investment (OFDI); Location Choice; Internationalization Process Model (IPM)